8-6(1-9f)=-30

Simple and best practice solution for 8-6(1-9f)=-30 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-6(1-9f)=-30 equation:


Simplifying
8 + -6(1 + -9f) = -30
8 + (1 * -6 + -9f * -6) = -30
8 + (-6 + 54f) = -30

Combine like terms: 8 + -6 = 2
2 + 54f = -30

Solving
2 + 54f = -30

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 54f = -30 + -2

Combine like terms: 2 + -2 = 0
0 + 54f = -30 + -2
54f = -30 + -2

Combine like terms: -30 + -2 = -32
54f = -32

Divide each side by '54'.
f = -0.5925925926

Simplifying
f = -0.5925925926

See similar equations:

| ab=5-5c | | 4r^4-8r^2+16= | | 0.3(3x-12)+11=1+1.5x | | 7x-12=15+4x | | 4r^4-8r^2=16 | | 8x+5=13x-6 | | x(6+10)=58 | | 540-14p=120 | | -2+8+x+(-12)=(-17)+9 | | 6x+11x-25+13x-35+6x+35+8x+15+9x-5+7x+15=900 | | 10x-4+4+4+x-22=0 | | 8-(-3-7x)-2(5x+3)=36 | | n^2+2n-19=5 | | fx+1=9x+4 | | 10(10+8k)= | | 0.6768%= | | f(x+1)=9x+4 | | x^2+-2x+-4=0 | | -6(2n-7)+2(n+4)=-36 | | x-2x-4=0 | | 20(x-0.5)=70 | | 26-18=2(x-2) | | 540-8P=120+6P | | 4(8a+-8)= | | 8z=12 | | 2x-sin(0.5x)=0 | | 7x-12=15-4x | | 8x-(x-4)=7x | | =6P+540 | | y^2-2y-35= | | 4t-2= | | x+18+4x=-10-4x-17 |

Equations solver categories